Reduction of ferric hemoglobin from Trematomus bernacchii in a partial bis-histidyl state produces a deoxy coordination even when encapsulated into the crystal phase. Issue 2 (2008) - Merlino Merlino, Antonello Antonello; Verde Verde, Cinzia Cinzia; di Prisco di Prisco, Guido Guido; Mazzarella Mazzarella, Lelio Lelio; Vergara Vergara, Alessandro Alessandro
Abstract : Crystallographic and spectroscopic evidences on Antarctic fish hemoglobins (AFHbs) have revealed that their ferric tetramers at physiological pH are in a mixed | α (aquo-met)/ β (bis-histidyl) coordination state and show a quaternary structure intermediate between the classical R and T states (H state). Ferric bis-histidyl adducts (hemichromes) have been also observed in some mammalian Hbs. In order to clarify whether hemichrome in AFHbs can be converted into a ferrous bis-histidyl adduct (hemochrome), at least in the crystal phase, chemical reduction of ferric hemoglobins from Trematomus bernacchii (HbTb) single crystals has been followed via Raman microscopy. The results of this analysis reveal that in HbTb, upon reduction, the bis-histidyl coordination is disrupted in favor of a penta-coordinated ferrous deoxy state, with no evidence of hemochrome. These data are in agreement with UV/Vis absorption spectra in solution. Furthermore, our data are also indirectly supported by the observation that upon reduction with dithionite, the ferric HbTb crystals crack and lose their diffraction power: in the crystalline state, the quaternary structure transition from the H to the T state is not compatible with the crystal packing. Altogether these data indicate that if bis-histidyl adducts have a functional significance in AFHbs, this function refers to a stable ferric state, or to a transient, though never detected, ferrous species.